2016
DOI: 10.1097/jnr.0000000000000131
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Turkish Nursing Students Related to Ageism

Abstract: The results from the Ageism Attitude Scale revealed that the participants held a generally positive attitude toward aging. It is of great importance to include more lessons on the older adults and the aging process and to increase activities to develop awareness of ageism, to help students develop positive attitudes and perspectives toward the care of the older adults. Because experience caring for the older adults is important in developing a positive attitude toward the older adults, arranging relevant clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 20 publications
2
22
1
4
Order By: Relevance
“…This score was assessed as a 'positive attitude' by the investigators who performed the study. The mean scores obtained in those studies using the same scale were as follows: 80.0 among nurses (14), 84.0-87.0 among students at a nursing school (17,18), 83.7 among the students of the Faculty of Economics and Administrative Sciences (19) and 70.6 among the students of the Vocational School of Health Services (20). The score obtained in a study that was performed in the general population was 80.2 (21).…”
Section: Discussionmentioning
confidence: 95%
“…This score was assessed as a 'positive attitude' by the investigators who performed the study. The mean scores obtained in those studies using the same scale were as follows: 80.0 among nurses (14), 84.0-87.0 among students at a nursing school (17,18), 83.7 among the students of the Faculty of Economics and Administrative Sciences (19) and 70.6 among the students of the Vocational School of Health Services (20). The score obtained in a study that was performed in the general population was 80.2 (21).…”
Section: Discussionmentioning
confidence: 95%
“…A study investigating ageist attitudes among nursing students, nurses, and physicians in the Turkish context demonstrated that Turkish healthcare providers' attitudes toward older individuals were generally positive (11)(12)(13). However, to the best of our knowledge, no studies have evaluated ageist attitudes of Turkish nursing staff and its relation with occupational burnout and job satisfaction.…”
Section: Ageism In Nursing Staffmentioning
confidence: 95%
“…Aynı çalışmada "İnsan yaşlandıkça çocuklaşır, küskünleşir, asabi, kavgacı ve alıngan olur", "Yaşlı insan evinde oturmalı, sakin bir yaşam sürdürmelidir" ve "Yaşlı için en uygunu çocukları ile birlikte yaşamasıdır" ifadelerine katılma oranlarının birinci sınıf öğrencilerinde daha yüksek olduğu saptanmıştır. Özdemir ve Bilgili'nin (23) (2016) yaptığı çalışmada ise yaşlılık kavramının hemşirelik öğrencileri için "hastalık, güçsüzlük, bağımlılık, yalnızlık, şevkat ve bağlılık" kavramlarını çağrıştırdığı belirlenmiştir. Bir başka çalışmada da hemşirelik öğrencilerinin yaşlılığı "hareketlerin yavaşlaması", "hızlı koşamayan", "immün sistem ve metabolizmanın yavaşlaması", "deneyimli", "unutkan, dikkatsizlik", "kendi işlerini gerçekleştiremeyen" ve "yoğun depresif duygular yaşayan" bireyler olarak algıladıkları belirlenmiştir.…”
Section: Sağlık Hizmetlerinde Yaşlılıkla İlgili İnanç Ve Tutumlarunclassified